Kajian Arkeologis Terhadap Jembatan Peninggalan Masa Kolonial di Desa Lebong Tandai, Kecamatan Napal Putih, Kabupaten Bengkulu Utara - Gaya Mentari (Badan Riset dan Inovasi Nasional (BRIN), 2022)
The archaeological remains in Lebong Tandai, Napal Putih District, North Bengkulu Regency are records that reflect the existence of human life in the past with distinctive cultural characteristics of its time. In this study, there was a discussion of archaeological remains in the form of an old bridge found in Lebong Tandai Village which was founded in the 19th century. As an effort to re-map the potential of archaeological remains in Lebong Tandai, the documentation of archaeological remains in the form of an old bridge in Lebong Tandai was the main problem studied in this study. The method used was a qualitative method by providing a comprehensive description of the archaeological object of the old bridge as a means of supporting mining activities and building structures that have a vital role in the activities of the local community at that time. The result of this study indicated that the old bridge in Lebong Tandai Village was a colonial bridge style. The bridge was built by the Dutch private mining company named Simau, in 1907.